The Nexus of Boycott Actions and Promotions on Sales Response and Purchasing Decisions: Evidence from McDonald’s in Indonesia - Mega Maharani; Lela Nurlaela Wati; Mohamad Lutfi (Research Synergy Foundation, 2025)
This study aims to analyze the influence of promotional activities and boycott actions on consumer purchasing decisions, with sales response serving as an intervening variable. The research approach applied is quantitative and causal, utilizing the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The population in this study consisted of McDonald's consumers in the DKI Jakarta area, with a sample size of 110 respondents, including 58 women and 52 men, selected using a purposive sampling technique. The results indicate that promotions have a positive and significant impact on sales response and purchase decisions. Conversely, boycotts have no impact on sales responses or purchasing decisions. This study examines the impact of promotions and boycotts on McDonald's purchasing behavior in DKI Jakarta. Utilizing sales response as the mediating variable, which has not been thoroughly discussed previously, the findings indicate that promotions exert a substantial influence, whilst boycotts do not affect outcomes. The Partial Least Squares Structural Equation Modeling (PLS-SEM) method offers an innovative perspective on marketing strategies and brand crisis management in Indonesia, facilitating more intricate analyses.